Sodium Caseinate Improves Emulsion Stability of Meat Model System Formulated with Pre-neutralized Red Palm Olein-canola Oil Emulsion Gel (Jurnal Ilmu dan Teknologi Hasil Ternak, 2023)
Replacing animal fat with vegetable fat in comminuted meat products often faces technological property challenges, such as high weight loss after cooking and a texture that is not dense and compact due to the predominant composition of unsaturated fatty acids. The use of emulsifiers from natural ingredients such as sodium caseinate can be a solution to improve the stability of the emulsion. In this research, sodium caseinate was added to the meat emulsion system at several levels: 0%, 0.15%, 0.30%, 0.45%, and 0.60% (w/w) of dough weight. The pH value, emulsion stability of the raw batter, cooking loss, texture profile and color of the final product were tested to prove the capabilities of sodium caseinate. The addition of 0.3% sodium caseinate improved emulsion stability, prevented excessive shrinkage and improved texture, without changing the color of the final product. In conclusion, the addition of sodium caseinate at 0.30% (w/w) is recommended in the manufacturing of comminuted meat products formulated with red palm-canola oil emulsion gel as animal fat replacer.